Coronary endarterectomy in coronary artery disease: Factors affecting graft patency and survival. (February 2022) - Chow, Simon CY; Ho, Jacky YK; Kwok, Micky WT; Fujikawa, Takuya; Lim, Kevin; Wan, Song; Wong, Randolph HL
Background: Coronary endarterectomy aims to improve completeness of revascularization in patients with occluded coronary vessels. The benefits of coronary endarterectomy remain uncertain. The aim of this study was to evaluate short-term surgical outcomes and factors affecting graft patency post-coronary endarterectomy. Methods: Between 2009 and 2019, 81 consecutive patients who had coronary endarterectomy done were evaluated for their perioperative and early results. A total of 36 patients with follow-up coronary studies were included in patency analysis. Mortality rates, major adverse cardiac and cerebrovascular events, and graft patency were outcomes of interest. Survival and risk factor analysis were performed with Kaplan–Meier and logistic regression analysis. Results: The average age of the cohort was 61.9 ± 9.29 years. Complete revascularization rate was 95.4% post-coronary endarterectomy. The 30-day and 1-year mortality was 2.5 and 6.2%, respectively. One-year major adverse cardiac and cerebrovascular events rate was 11.1%. Periprocedural myocardial infarction rate was 7.4%. Three patients required repeat revascularization within a mean follow-up duration of 49.6 ± 36.5 months. Overall graft patency was 89.2% at 20.2 months and graft patency post-coronary endarterectomy was 85.4%. Arterial grafts showed 100% patency. Vein grafts to endarterectomized obtuse marginal branch had patency rates of 33.3%. Multiple endarterectomies were associated with worse one-year major adverse cardiac and cerebrovascular events (OR: 28.6 ± 1.16; P  = 0.003). Conclusions: Coronary endarterectomy facilitates completeness of revascularization and does not increase early mortality. Graft patency post-coronary endarterectomy on obtuse marginal artery was suboptimal. Judicious use of coronary endarterectomy should be practiced to balance the need of completeness of revascularization against the risk of myocardial infarction.